1939
DOI: 10.1084/jem.69.6.767
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Sensitization of Animals With Simple Chemical Compounds

Abstract: One of the open questions concerning skin sensitization of the "contact dermatitis" type to simple chemical compounds is in which way sensitivity spreads all over the integument when only a given area is treated. This subject has been considered in a paper by Simon (1) and studied experimentally. The skin of guinea pigs was treated with concentrated nitric acid in such manner that a complete belt severed the continuity of the epidermis. Poison ivy extract was applied on the posterior part of the animals and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

1940
1940
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 15 publications
1
19
0
2
Order By: Relevance
“…Half-body x-ray given 3 days after allergen depressed the resultant sensitivity if the x-ray field included the lymph nodes regional to the sensitization site; similar x-ray administered shortly be fore allergen was ineffective. This result is consistent with a number of studies that have demonstrated the importance of the lymph nodes regional to the sensitization site during the induction of DTH [7,8,11]. These nodes are the main sites for the se questration and clonalization of T cells se lected by antigen; regional lymphadenectomy during the induction of DTH prevents the acquisition of sensitivity [12].…”
supporting
confidence: 90%
“…Half-body x-ray given 3 days after allergen depressed the resultant sensitivity if the x-ray field included the lymph nodes regional to the sensitization site; similar x-ray administered shortly be fore allergen was ineffective. This result is consistent with a number of studies that have demonstrated the importance of the lymph nodes regional to the sensitization site during the induction of DTH [7,8,11]. These nodes are the main sites for the se questration and clonalization of T cells se lected by antigen; regional lymphadenectomy during the induction of DTH prevents the acquisition of sensitivity [12].…”
supporting
confidence: 90%
“…Thus in earlier experiments of Landsteiner and Chase (12), patent lymphatics were required for initiating delayed sensitivity when ivy extract was applied on an isolated skin island. Not conceived then, the alternative explanation of peripheral sensitization and use of the lymphatic pathway for passage of newly "informed" cells into regional 1 For coupling of hapten in situ, information available on picryl chloride indicates that under physiological conditions (11) relatively high molar ratios of PC1 to protein are needed.…”
Section: The Development Of Contact Sensitivitymentioning
confidence: 89%
“…The chemistry of protein haptenation has been investigated for about 70 years [22,23] , by Mayer in the 1950s [24] , by the breakthrough collaboration of Dupuis and Benezra at the beginning of the 1980s [25] , and in the 1990s and this century by Lepoittevin and colleagues [26][27][28][29][30] . However, a major step change occurred with the seminal publication of Roberts and Williams in 1982 [31] which combined chemistry with mathematical insights to yield quantitative structure-activity relationships.…”
Section: Pathogenetic and Molecular Aspects Of Skin Sensitizationmentioning
confidence: 99%